PREDIKSI PRESENT SERVICEABILITY INDEX UNTUK ANALISIS SISA UMUR LAYAN PERKERASAN LENTUR - Hesti Ratnasari; Latif Budi Suparma (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2021)
Abstract Present Serviceability Index is a measure of pavement performance and can be used as an indicator of timing and maintenance requirements. This study aims to determine and predict the Present Serviceability Index value during the pavement design life. The amount of the structural response due to loading was analyzed using an empirical mechanistic method with the help of KENPAVE software. The results of the structural response are used to calculate the magnitude of cracking and rutting damages, which are then used to predict the value of the International Roughness Index. The predicted International Roughness Index values were then statistically tested with the results of field measurements for the last 4 years. Furthermore, the Present Serviceability Index value was analyzed based on the prediction results of the International Roughness Index values. This study shows that the pavement has reached terminal serviceability in year 5.2 and requires strengthening. The prediction results of the Present Serviceability Index value with the implementation of overlays as thick as 10 cm in the 5.2nd year show that the terminal serviceability is achieved in the 9.5th year, thus increasing the service life of the road by 4.3 years. Keywords: pavement performance; cracking; routines; Present Serviceability Index; serviceability terminals. Abstrak Present Serviceability Index merupakan suatu ukuran kinerja perkerasan jalan dan dapat digunakan sebagai indikator penentuan waktu dan kebutuhan pemeliharaan. Studi ini bertujuan menentukan dan memprediksi nilai Present Serviceability Index selama umur rencana. Besarnya respons struktur akibat pembebanan dianalisis menggunakan metode mekanistik empiris dengan bantuan software KENPAVE. Hasil respons struktur digunakan untuk menghitung besarnya kerusakan-kerusakan cracking dan rutting, yang selanjutnya digunakan untuk memprediksi nilai International Roughness Index. Nilai International Roughness Index hasil prediksi kemudian diuji statistika dengan hasil pengukuran lapangan selama 4 tahun terakhir. Selanjutnya, nilai Present Serviceability Index dianalisis berdasarkan hasil prediksi nilai International Roughness Index. Studi ini menunjukkan bahwa perkerasan telah mencapai terminal serviceability pada tahun ke-5,2 dan memerlukan penguatan. Hasil prediksi nilai Present Serviceability Index dengan penanganan overlay setebal 10 cm pada tahun ke-5,2 menunjukkan bahwa terminal serviceability tercapai pada tahun ke-9,5, sehingga menambah umur layan jalan sebesar 4,3 tahun. Kata-kata kunci: kinerja perkerasan jalan; cracking; rutting; Present Serviceability Index; terminal service-ability.